И.ЮСУПОВ ЛИРИКАЛАРЫНДА ПЕРИФРАЗАЛАРДЫҢ ОБРАЗ ЖАСАЎДАҒЫ ХЫЗМЕТИ - Отепбергенова, Г. (SCIENCE and SOCIETY, 2024)
The article presents comments on a special type of artistic means, periphrasis. There is tachen info account theoretical views of foreign scientists on the theory of periphrasis. The types of periphrasis are discussed in the work of the poet I. Yusupov and its poetic image, emotional-expressive service
Keywords: I.Yusupov's lyrics; periphrasis; types of periphrasis